Clinical Utility of Pretreatment and 3-Month 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Standardized Uptake Value in Predicting and Assessing Recurrence in T3-T4 Laryngeal Carcinoma Treated With Definitive Radiation. (July 2019) - Mayo, Zachary; Seyedin, Steven N.; Mallak, Nadine; Mott, Sarah L.; Menda, Yusuf; Graham, Michael; Anderson, Carryn
Objectives: The aim of this study was to investigate the utility of pretreatment and 3-month 18 F-fluorodeoxyglucose positron emission tomography (PET)/computed tomography (CT) standardized uptake value (SUV) in predicting and assessing recurrence in T3-T4 laryngeal carcinoma treated with definitive radiation therapy (RT). Methods: Patients with newly diagnosed T3-T4 laryngeal squamous cell carcinoma treated with definitive RT from 2004 to 2014 were reviewed. Patients who underwent pretreatment or 3-month PET/CT 2 to 4 months after treatment were included. Those with prior systemic, surgical, or RT treatment were excluded. The primary objective was to assess whether pretreatment or posttreatment maximum SUV of the primary site (pSUV) of disease was associated with local recurrence-free survival. Overall survival was a secondary end point. Sensitivity, specificity, positive predictive value, and negative predictive value were calculated to assess the accuracy of 3-month PET/CT at the larynx primary. Results: Twenty-eight patients were eligible for analysis. Median follow-up time was 34.7 months (range, 5.3-138.7 months), and median age was 57 years. Most patients had supraglottic (71.4%), T3 (89.3%), N2 (50.0%) disease, received chemotherapy (96.4%), and had histories of tobacco use (96.4%). On univariate analysis, 3-month posttreatment pSUV was associated with local recurrence-free survival ( P < .01), while pretreatment pSUV was not ( P = .41). No other associations were found with local recurrence-free survival. Neither pretreatment nor 3-month pSUV was significantly associated with overall survival. The calculated sensitivity, specificity, positive predictive value, and negative predictive value of 3-month PET/CT at the primary site were 33%, 85%, 40%, and 81%, respectively. Conclusions: High initial fluorodeoxyglucose uptake in T3-T4 laryngeal primaries did not show an association with the risk for postradiation local relapse or overall survival, while increased fluorodeoxyglucose uptake at 3 months was associated with increased local recurrence. At 3 months, the relatively low sensitivity and positive predictive value may limit the utility of PET/CT in the assessment of persistent advanced laryngeal cancer after definitive radiation.